The Splendor and Divine Mastery of Allah's Creation: A Reflection on the Camel: روعة وإتقان خلق الله: تأمل فى الإبل - Ismail Abdul Ghani al-Jalal (Walidem Institute and Publishing (WIP), 2025)
Objective: This study examines the splendour and divine mastery reflected in the creation of the camel, highlighting its unique design and functionality as evidence of Allah’s signs in creation. The research aims to deepen understanding of the camel’s exceptional features from both theological and scientific perspectives, emphasizing its role in Islamic teachings as a symbol of reflection on God’s power. Theoretical framework: The theoretical framework combines Quranic verses and hadiths related to creation with modern scientific perspectives on the camel’s biological and ecological adaptations. Literature Review: The literature review encompasses previous studies that discuss the interconnection between the wonders of nature and the reinforcement of faith. Methods: The study employs a multidisciplinary approach, integrating textual analysis of Islamic sources with modern scientific research on the physiology and ecology of camels. The primary issue addressed is the lack of awareness among contemporary audiences about the profound lessons embedded in the natural world, particularly in the camel’s unique design. Results: The findings reveal that the camel’s physiological characteristics—such as its ability to endure extreme desert conditions, extraordinary water retention mechanisms, and efficient energy usage—serve as clear evidence of the deliberate and intricate design by the Creator. Implications: The study underscores the importance of reflecting on such creations to strengthen faith, foster gratitude, and inspire a harmonious relationship with nature. Novelty: The novelty of this research lies in its holistic approach, which integrates Islamic theology with modern science to demonstrate the divine wisdom underlying the natural world. This paper encourages a renewed appreciation for the marvels of creation, urging readers to look beyond the physical aspects and recognize the divine wisdom embedded in the universe.